Eksplorasi Visual Flora dan Fauna dalam Ilustrasi Kontemporer Berbasis Medium Gutta Tamarind Diatas Kain Armani - Olivedia Justin Wijaya; Diva Graciella Augusta Nafi; Laurens Enrico Djenmakani; Basituasi Baene; Karen Christl Wen; Wawan Suryana (Ideas Publishing, 2025)
This study discusses the visual exploration of flora and fauna in contemporary illustrations based on Armani fabric using the gutta tamarind technique. The purpose of this study is to identify the visual advantages of natural organic forms when processed through a creative experimental approach in textile painting courses. The method used is a creative experimental method with an artistic approach that includes four stages, namely visual exploration, creation of works, analysis of works, and conclusions. Visual exploration is carried out through visual observation, data collection, and literature studies with relevant sources. The creation stage focuses on the application of the gutta tamarind cold wax technique and the exploration of natural and pastel colors. The use of cold wax includes the stages of line formation, coloring, drying, and repeated washing within a period of one to two weeks. The analysis of the work emphasizes that the combination of the entire process can create imaginative visuals. The results of this study confirm that the gutta tamarind technique on Armani fabric has the potential to produce distinctive and unique visual qualities through a combination of lines, motifs, shapes, textures, and colors. Although the gutta tamarind technique is not yet widely used, the findings of this study can be a source of information that can be used and developed further by the community in the process of community development and art practice